(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this article a method of obtaining an experiment plan in a fragment of multidimensional space is analyzed and improved. The method is based on an assumption that particles will distribute evenly in an infinite space with constant charged particle density. To obtain the experiment plan, the infinite multidimensional space is replaced with a hypercube whose surface models influence of the surrounding infinite space. Software is developed and practical results in obtaining experiment plan in two-dimensional space are acquired. Two-dimensional space allows developing of a methodology and algorithm for obtaining experiment plan while providing a simple visualization of the solution. Acquired results in two-dimensional space give an opportunity to create methods for obtaining experiment plan in a hypercube of multidimensional space.